Perspectives of psychiatric nurses on the stigmatization of mental healthcare in Ghana: a qualitative study - Mensah, David Kofi (Frontiers in Public Health, 2024)
Background Stigma surrounding mental illness has been identified as a major bane of psychiatric care in many low- and middle-income countries. Mental illness stigma affects both the sufferer and their care providers, including families and psychiatric care providers. In Ghana, attention toward psychiatric care is limited. This article provides qualitative insights on interpersonal and structural stigma experiences of psychiatric nurses from the Ankaful Psychiatric Hospital, Ghana, and the impact of these stigmas on psychiatric care provision in Ghana. The article addresses relevant gap in the literature on the impact of mental illness stigma experiences among psychiatric nurses in low- and middle-income countries. Methods Using a qualitative research approach, this study draws from the experiences and perspectives of stigma among psychiatric nurses from the Ankaful Psychiatric Hospital. Fourteen registered psychiatric nurses were recruited and interviewed using semi-structured interviews with open-ended questions. A thematic analysis approach was adopted to analyze the data. Coding and analysis were done in NVivo 12, aiding in the analysis of major themes and subthemes that emerged from the data. The study was conducted remotely due to the COVID-19 pandemic travel restrictions. Results Themes identified include social and structural stigmas toward psychiatric nurses and the impact of these stigmas on mental healthcare in Ghana. While social stigma makes psychiatric nursing a difficult career choice for many, structural stigma—resulting from governmental neglect and lack of material resource provision—presents difficulties for nurses and other psychiatric care providers in the exercise of their care duties, which negatively impacts care provision for persons with mental health issues. Conclusion The relevance of the experiences and perspectives of psychiatric nurses on mental illness stigma cannot be overlooked in the effort to promote mental illness advocacy, treatment seeking, and improve psychiatry. This article provides insights into the stigma experiences of psychiatric nurses and the impact of these stigmas on mental healthcare provision in Ghana. The study contributes to efforts to improve mental healthcare policymaking and advocacy.